Survival benefit of ghrelin in the heart failure due to dilated cardiomyopathy. Issue 5 (October 2014) - Du, Cheng‐Kun; Zhan, Dong‐Yun; Morimoto, Sachio; Akiyama, Tsuyoshi; Schwenke, Daryl O.; Hosoda, Hiroshi; Kangawa, Kenji; Shirai, Mikiyasu
Abstract Although ghrelin has been demonstrated to improve cardiac function in heart failure, its therapeutic efficacy on the life expectancy remains unknown. We aim to examine whether ghrelin can improve the life survival in heart failure using a mouse model of inherited dilated cardiomyopathy (DCM) caused by a deletion mutation ΔK210 in cardiac troponin T (cTnT). From 30 days of age, ghrelin (150 μg/kg) was administered subcutaneously to DCM mice once daily, control mice received saline only. The survival rates were compared between the two groups for 30 days. After 30‐day treatment, functional and morphological measurements were conducted. Ghrelin‐treated DCM mice had significantly prolonged life spans compared with saline‐treated control DCM mice. Echocardiography showed that ghrelin reduced left ventricular (LV) end‐diastolic dimensions and increased LV ejection fraction. Moreover, histoanatomical data revealed that ghrelin decreased the heart‐to‐body weight ratio, prevented cardiac remodeling and fibrosis, and markedly decreased the expression of brain natriuretic peptide. Telemetry recording and heart rate variability analysis showed that ghrelin suppressed the excessive cardiac sympathetic nerve activity (CSNA) and recovered the cardiac parasympathetic nerve activity. These results suggest that ghrelin has therapeutic benefits for survival as well as for the cardiac function and remodeling in heart failure probably through suppression of CSNA and recovery of cardiac parasympathetic nerve activity.